PERSEPSI REMAJA KOTA SURABAYA TERHADAP PRODUK BATIK - Parwita Setya Wardhani (Politeknik Negeri Sriwijaya, 2014)
Batik is one of the culture of the nations that should keep preserved. Since the days of the kingdom and batik have been living and developing has been proven by relief-relief which is found on the wall of the temples. Shades of batik and variation produced was adapted to the philosophy and culture each regions. The role of the wider community is to continue maintaining and preserving Batik. Not only the adults people but also the young generation and teenagers have to come to support this culture. this study conducted to get answers to the question how is the perception of teenagers throughout Surabaya towards batik products. This study using methods of quantitative with an analysis descriptive statistics , and the sample collected done is randomly .The results of the analysis in this research we can conclude that the perception of teenagers to products of batik is very positive. Most of teenagers in Surabaya have a batik product, and wearing it without embarrassed, while they participated in promoting of batik products. However, they want the batik product packed that accordance with their tastes, including its design and the type of products is not limited to clothing developed into a product that is often they used in daily activities, like bags, accessories and so on. Intentionally, the result of this analysis suggest for the society, artisans, businessmen to introduce and designers and placing the products on the market. Thus batik as the culture of the nations can be continuously maintained